A Quasi-Experimental Analysis of Elementary School Absences and Fine Particulate Air Pollution. Issue 9 (March 2016) - Hales, Nicholas M.; Barton, Caleb C.; Ransom, Michael R.; Allen, Ryan T.; Pope, C. Arden
Abstract : Abstract: Fine particulate air pollution (PM2.5 ) has been associated with many adverse health outcomes including school absences. Specifically, a previous study in the Utah Valley area, conducted during a time with relatively high air pollution exposure, found significant positive correlations between school absences and air pollution. We examined the hypothesis that ambient PM2.5 exposures are associated with elementary school absences using a quasi-natural experiment to help control for observed and unobserved structural factors that influence school absences. The Alpine, Provo, and Salt Lake City school districts are located in valleys subject to daily mean PM2.5 concentrations almost twice as high as those in the Park City School District. We used seminonparametric generalized additive Poisson regression models to evaluate associations between absences and daily PM2.5 levels in the 3 districts that were exposed to the most pollution while using Park City absences as a quasi-control. The study covered 3 school years (2011/12-2013/14). School absences were most strongly associated with observed structural factors such as seasonal trends across school years, day-of-week effects, holiday effects, weather, etc. However, after controlling for these structural factors directly and using a control district, a 10 μg/m 3 increase in PM2.5 was associated with an approximately 1.7% increase in daily elementary school absences. Exposure to ambient air pollution can contribute to elementary school absences, although this effect is difficult to disentangle from various other factors.